EFFECTIVENESS OF PRENATAL YOGA ON LEVEL DISCOMFORT OF PREGNANT WOMEN TM III IN PMB MIDWIFE UMROH GROGOL SUKOHARJO - Pramita Sandy Ulya Imannura; Enyk Yunanto; Anna Mariyana (Universitas STRADA Indonesia, 2023)
Yoga is done with deep breathing so that it increases the flow of oxygen to the brain so that it can reduce anxiety, depression, psychological disorders, and symptoms of pain including low back pain.The research method used is an experimental design method, with one group pretest-posttest design. The study used primary data, a sample of 30 third-trimester pregnant women, divided into 2 groups, namely the experimental group 15 respondents, and the control group 15 respondents. The independent variable is prenatal yoga. The dependent variable is the discomfort of pregnant women. Data analysis used normality, homogeneity, Wilcoxon, and Mann-Whitney tests.The data in the pre-test showed abnormal results (control group (p=0.004) and experimental group (p=0.000) and homogeneous (p=0.972).The results of the data analysis showed that there was the effectiveness of prenatal yoga on the level of discomfort of pregnant women at different post-test and pre-test (p = 0.000).